The chameleon of neuroinflammation: magnetic resonance imaging characteristics of natalizumab-associated progressive multifocal leukoencephalopathy - Wattjes, Mike P; Richert, Nancy D; Killestein, Joep; de Vos, Marlieke; Sanchez, Esther; Snaebjornsson, Petur; Cadavid, Diego; Barkhof, Frederik (Multiple sclerosis, 2013)
Natalizumab is a monoclonal antibody against α4-integrin approved for the treatment of multiple sclerosis (MS) due to a positive effect on clinical and magnetic resonance imaging (MRI) outcome measures. However, one relatively rare but serious side effect of this drug is a higher risk of developing progressive multifocal leukoencephalopathy (PML). Since the FDA approval, more than 300 natalizumab-associated PML cases have been documented among more than 100,000 treated MS patients. MRI is a crucial tool in the surveillance of patients treated with natalizumab in order to detect possible signs of PML in the asymptomatic stage. Although classical imaging characteristics of PML are well established, MRI findings in natalizumab-associated PML, particularly in early disease stages, show rather new and heterogeneous imaging findings including different patterns of inflammation with contrast enhancement. This review provides a comprehensive overview of the heterogeneous imaging findings in natalizumab-associated PML in the context of the underlying pathophysiology, histopathology, and the diagnostic procedure. We describe the MRI patterns of PML lesion evolution and complications including immune reconstitution inflammatory syndrome (IRIS). Finally, we present guidelines to differentiate MRI findings in PML from inflammatory demyelinating lesions, to facilitate the early diagnosis of PML in patients treated with natalizumab.